Semantic Similarity Detection in a Single Text - Polityuk, Anna; Orobinska, Olena (My University, 2020)
To solve many of the problems of automatic natural language processing, it is often necessary to have a dictionary of synonymous terms. To simplify its using is objective of our experiment. We propose the method that realize the lexical approach and provide the detecting all synonyms in a single text and visualize the results directly in the text. The results depend on the completeness of the lexical source. But it is a bottleneck problem of most of thesaurus.
Keywords: semantic similarity; synonymy; semantic closeness; proximity metric; thesaurus; single text